ORGANIZATIONAL PERFORMANCE DAN SUPPLY CHAIN MANAGEMENT PADA ORGANISASI - irfangi, Ahmad; Riswanto, Beny; Edy Sahputro, Slamet Cahyo; Toif Arbi, Mohammad (Jurnal Teknologi dan Bisnis, 2020)
The purpose of this study was to examine the effect of supply chain management on organizational performance. This research uses data from 32 organizations engaged in brown sugar production in Central Java through www.googledocs.com. Analysis using structural equation information sharing (SEM). The results showed that information sharing, cooperation and integration process had a positive and significant effect on organizational performance. However, longterm relations proved to have no significant effect on organizational performance.